URBAN FARMING IN THE CONTEXT OF INCREASING COMMUNITY WELFARE AND PARTICIPATION THROUGH THE WOMEN’S FARMERS GROUP (KWT) OF SAUYUNAN GARDENS COMMUNITY - Tita Rosita; Agus Hasbi Noor (IKIP Siliwangi Bandung, 2020)
This study examines the implementation of urban agriculture called urban farming. Urban agriculture is the practice of cultivating, processing, and distributing food around the city carried out by women who are being parted healthy heart community. Urban agriculture also includes livestock, aquaculture, agroforestry, and horticulture. In the broadest sense, urban agriculture describes the entire system of food production that occurs in cities. The purpose of this study is to initiate the awareness of the community and have an active role in implementing and managing degraded land through urban farming programs, And also can take a benefit by managing available land to become a farming place, and finally people realize that by managing land or yard around their house can add give income and increase economic value, besides that the community members who are able to process various crops from their gardens into foods that have high selling value by marketing them online. RW 03 region of Sarijadi does not have large land to cultivate, because the existing field is used by residents to park four-wheeled vehicles. So that the facilities for sports used by residents are also very limited. Thus the method used to attract residents to participate in the urban farming program which was initiated by the head of RW 03 region of Sarijadi in collaboration with KJS Melati is managing the degraded land around the outskirts of the field to become gardens. The method used in this research is a descriptive method, namely the method that focuses on the problems that exist in the meantime. This is in accordance with the opinion of Winarno Surakhmad (1982: 140) who argues that descriptive methods have characteristics: Focusing on solving problems that exist in the present time, and solve actual problems. The collected data then being compiled, explained, then analyzed (because this method often called as the analysis method). Based on the opinion above, the descriptive method is used to describe the condition of the implementation of increasing community participation in the urban farming program RW 03 Region of Sarijadi. Most of the urban citizen is careless toward the degraded land or limited land around their neighborhoods because most of the citizen are busy with their job at home or at the workplace.